Cloning and sequence analysis of cDNA for the canine neurotensin/neuromedin N precursor. - Dobner, P R (1987)
Cloned cDNAs encoding neurotensin were isolated from a cDNA library derived from primary cultures of canine enteric mucosa cells. Nucleotide sequence analysis has revealed the primary structure of a 170-amino acid precursor protein that encodes both neurotensin and the neurotensin-like peptide neuromedin N. The peptide-coding domains are located in tandem near the carboxyl terminus of the precursor and are bounded and separated by the paired, basic amino acid residues Lys-Arg. An additional coding domain, resembling neuromedin N, occurs immediately after an Arg-Arg basic amino acid pair located in the central region of the precursor. Additional amino acid homologies suggest that tandem duplications have contributed to the structure of the gene. RNA blot analysis, using the cloned cDNA probe, has revealed several mRNA species ranging in size from 500 to 980 nucleotides in the canine enteric mucosa. In contrast, a single RNA species of 1500 nucleotides was detected in bovine hypothalamus poly(A)+ RNA. The ability of the canine probe to cross-hybridize with bovine mRNA suggests that this probe can be used to isolate neurotensin/neuromedin N genes from other mammalian species.